Peningkatan Aktivitas Pasar Tradisional Melalui Bazar UMKM dan Pemanfaatan Media Sosial sebagai Strategi Digitalisasi di Talang Padang - Naufal Rafiqi Anas; Eka Lediyana; Angga Febrian; Laili Fadhila Banuwa; Mutiasari Nur Wulan; Ahmad Hudalil; Megasari Megasari (Fakultas Sains Dan Teknologi, Universitas Raden Rahmat Malang, 2025)
This study aims to explore digitalization strategies for traditional markets, particularly in optimizing the potential of local micro, small, and medium enterprises (MSMEs) at Talang Padang Market. The objective is to examine the implementation of digital marketing through social media as a promotional tool to enhance economic activity in the market. The methods employed include field observation, interviews with stakeholders, and the execution of an MSME bazaar involving market managers and MSME actors. Promotion efforts leveraged social media platforms to reach a broader audience and increase community engagement. The results indicate that social media effectively attracted more visitors and bazaar participants, leading to an increase in transactions and the sustainability of MSMEs. By the end of the program, 15 out of 36 MSMEs continued operating in Talang Padang Market, highlighting the long-term success of market digitalization strategies. Based on the evaluation, it is concluded that strengthening digital marketing and providing independent training for MSME actors are crucial to supporting the sustainability of traditional markets in the digital era. Therefore, collaboration among stakeholders is expected to continuously drive the development of the market and local MSMEs. Keywords: Traditional Market, Digital Marketing, Social Media, MSME’s.